Sob a condição que continue em nossa companhia : as décadas finais da escravidão e a transição para o trabalho livre em um município rio-grandense (Cachoeira, 1871/1889) - Sônego, Aline (2011)
This Master s dissertation proposes to analyze last decades of slavery and the transition to workforce free at rio-grandense city of Cachoeira, in the period from 1871 to 1889. From the perspective of Regional History, this work found to perceive which singularities the elimination of the slavery structure presented in an economic farming city. Three types of documental sources considered fundamental to investigate the process were used in this research: post-mortem stocks, manumission letters and the Register book of servant contract, which were quantitative and qualitative analyzed. From the stocks it was possible to identify social and economic configuration of the studied region and analyze the patrimonial structure in which slavery was established. Manumission letters, in its turn, contribute in the perception of the dynamic of relationship between lords and slavers in relation to concession and conquer of liberty. At last, by the Register book of servant contract, it was found to remind lord strategies to guarantee the domination over the incipient workforce free